3,5,3′-Triiodo-L-Thyronine- and 3,5-Diiodo-L-Thyronine- Affected Metabolic Pathways in Liver of LDL Receptor Deficient Mice - Moreno, Maria; Silvestri, Elena; Coppola, Maria; Goldberg, Ira J.; Huang, Li-Shin; Salzano, Anna M.; D'Angelo, Fulvio; Ehrenkranz, Joel R.; Goglia, Fernando (Frontiers in Physiology, 2016)
3,5,3’-triiodo-L-thyronine (T3) and 3,5-diiodo-L-thyronine (T2), when administered to a model of familial hypercholesterolemia, i.e. low density lipoprotein receptor (LDLr)-knockout (Ldlr-/-) mice fed with a Western type diet (WTD), dramatically reduce circulating total and very low-density lipoprotein/LDL cholesterol with decreased liver apolipoprotein B (ApoB) production. The aim of the study was to highlight putative molecular mechanisms to manage cholesterol levels in the absence of LDLr. A comprehensive comparative profiling of changes in expression of soluble proteins in livers from Ldlr-/- mice treated with either T3 or T2 was performed. From a total proteome of 450 liver proteins, 25 identified proteins were affected by both T2 and T3, 18 only by T3 and 9 only by T2. Using in silico analyses, an overlap was observed with 11/14 pathways common to both iodothyronines, with T2 and T3 preferentially altering sub-networks centered around hepatocyte nuclear factor 4 α (HNF4α) and peroxisome proliferator-activated receptor α (PPARα), respectively. Both T2 and T3 administration significantly reduced nuclear HNF4α protein content, while T2, but not T3, decreased the expression levels of the HNFα transcriptional coactivator PGC-1α. Lower PPARα levels were found only following T3 treatment while both T3 and T2 lowered liver X receptor α (LXRα) nuclear content. Overall, this study, although it was not meant to investigate the use of T2 and T3 as a therapeutic agent, provides novel insights into the regulation of hepatic metabolic pathways involved in T3- and T2-driven cholesterol reduction in Ldlr-/- mice.